Completing the banking union with a European deposit insurance scheme: Who is afraid of cross-subsidisation? - Jacopo Carmassi; Sonja Dobkowitz; Johanne Evrard; Laura Parisi; André Silva; Michael Wedow (European Central Bank (ECB), 2018)
On 24 November 2015, the European Commission published a proposal to establish a European Deposit Insurance Scheme (EDIS). The proposal provides for the creation of a Deposit Insurance Fund (DIF) with a target size of 0.8% of covered deposits in the euro area and the progressive mutualisation of its resources until a fully-fledged scheme is introduced by 2024. This paper investigates the potential impact and appropriateness of several features of EDIS in the steady state. The main findings are the following: first, a fully-funded DIF would be sufficient to cover payouts even in a severe banking crisis. Second, risk-based contributions can and should internalise specificities of banks and banking systems. This would tackle moral hazard and facilitate moving forward with risk sharing measures towards the completion of the Banking Union in parallel with risk reduction measures; this approach would also be preferable to lowering the target level of the DIF to take into account banking system specificities. Third, smaller and larger banks would not excessively contribute to EDIS relative to the amount of covered deposits in their balance sheet. Fourth, there would be no unwarranted systematic cross-subsidisation within EDIS in the sense of some banking systems systematically contributing less than they would benefit from the DIF. This result holds also when country-specific shocks are simulated. Fifth, under a mixed deposit insurance scheme composed of national deposit insurance funds bearing the first burden and a European deposit insurance fund intervening only afterwards, cross-subsidisation would increase relative to a fully-fledged EDIS. The key drivers behind these results are: i) a significant risk-reduction in the banking system and increase in banks' loss-absorbing capacity in the aftermath of the global financial crisis; ii) a super priority for covered deposits, further contributing to protect EDIS; iii) an appropriate design of risk-based contributions, benchmarked at the euro area level, following a "polluter-pays" approach.
Keywords: G21; G28; 330; European Deposit Insurance Scheme (EDIS); risk-based contributions; cross-subsidisation